2023
DOI: 10.3390/genes14061274
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Death-Associated Protein Kinase-1 in Cell Homeostasis-Related Processes

Abstract: Tremendous amount of financial resources and manpower have been invested to understand the function of numerous genes that are deregulated during the carcinogenesis process, which can be targeted for anticancer therapeutic interventions. Death-associated protein kinase 1 (DAPK-1) is one of the genes that have shown potential as biomarkers for cancer treatment. It is a member of the kinase family, which also includes Death-associated protein kinase 2 (DAPK-2), Death-associated protein kinase 3 (DAPK-3), Death-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…RARβ, in response to retinoic acid binding, can activate or repress the expression of target genes involved in various cellular processes, including cell cycle regulation, cell differentiation, proliferation, and apoptosis [ 19 ]. The DAPK gene, which encodes a serine/threonine kinase, is an inducer of cell death in response to different stimuli, including stress, DNA damage, and cytokines [ 20 ]. APC is essential in modulating cell growth and division, primarily by controlling the Wnt signaling pathway [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…RARβ, in response to retinoic acid binding, can activate or repress the expression of target genes involved in various cellular processes, including cell cycle regulation, cell differentiation, proliferation, and apoptosis [ 19 ]. The DAPK gene, which encodes a serine/threonine kinase, is an inducer of cell death in response to different stimuli, including stress, DNA damage, and cytokines [ 20 ]. APC is essential in modulating cell growth and division, primarily by controlling the Wnt signaling pathway [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…DAPK-1 suppression has an impact on apoptosis, which, in turn, contributes to the genesis and progression of cancer. Cells lacking DAPK-1 expression as a result of promoter hypermethylation exhibit increased invasiveness and metastatic potential [ 1 ]. There is not always a direct relationship between the methylation status and expression of the DAPK-1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…DAPK-1 was initially identified as a facilitator of cell death [ 1 ]. Prior research demonstrated that the downregulation of DAPK-1 expression effectively inhibited γ interferon-induced apoptotic cell death in HeLa cells (immortalized cell line).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation